Application of optical coherence tomography in cardiovascular diseases: bibliometric and meta-analysis - Lian, Wenjing; Chen, Cong; Wang, Jie; Li, Jun; Liu, Chao; Zhu, Xueying (Frontiers in Cardiovascular Medicine, 2024)
Since the advent of Optical Coherence Tomography (OCT) two decades ago, there has been substantial advancement in our understanding of intravascular biology. Identifying culprit lesion pathology through OCT could precipitate a paradigm shift in the treatment of patients with Acute Coronary Syndrome. Given the technical prowess of OCT in the realm of cardiology, bibliometric analysis can reveal trends and research focal points in the application of OCT for cardiovascular diseases. Concurrently, meta-analyses provide a more comprehensive evidentiary base, supporting the clinical efficacy of OCT-guided Percutaneous Coronary Intervention (PCI).